COMMUNITY SYMPATHY-BASED SLUM SANITATION PLANNING CONCEPT IN BATU BARA DISTRICT, NORTH SUMATERA, INDONESIA - Akus Harmoko; Abdiyanto; Cut Nuraini; Abdi Sugiarto (International Journal on Livable Space, 2024)
ABSTRACT Slums in the Tanjung Tiram area of Batu Bara Regency are caused by high and uneven population density, limited habitable land and low awareness of environmental conservation among residents. This results in poor environmental sanitation and potentially affects environmental sustainability. The local government is trying to improve this situation through slum upgrading and community empowerment programs. Objectives: This study aims to examine community sympathy for the spatial concept and environmental sanitation improvement programs in Tanjung Tiram neighborhood, as well as the factors that influence it. Methodology and Results: The research method was qualitative with a rationalist approach. The study began with literature analysis and continued with field studies to describe community sympathy in sanitation management, identify patterns of behavior change, and analyze the factors that influence it. Conclusion, Significance, and Implication: The results highlight that the community demonstrated empathy through responsibility and mutual concern for the interests of others, such as involvement in the sanitation improvement process from preparation to monitoring in terms of toilet and bathroom use. Community motivation comes from cadre interventions that provide understanding, increase empathy and responsibility, and strengthen community motivation in sanitation management. Community cooperation and awareness must be increased through community empowerment programs.